Economic and Social Survey of Asia and the Pacific 2016 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2016)
The Survey 2016 assesses the region’s outlook as it navigates through global uncertainties, providing policy options and strategies to support countries in striving towards achieving the Sustainable Development Goals. The report analyses a wide range of areas including economic growth, inflation, trade and investment, financial markets, inequality, employment, and environmental concerns. The special theme of Survey 2016 highlights how both economic growth and productivity growth have declined in the aftermath of the 2008 economic and financial crisis in the Asia-Pacific region. In doing so, the report examines underlying trends of productivity growth and argues that the 2030 Agenda for sustainable development provides an entry point to strengthen productivity as investing in the SDGs can foster productivity growth, thereby creating a virtuous cycle between sustainable development, productivity and development.